Cytokine Protocols - De Ley, Marc.; De Ley, Marc. (Methods in Molecular Biology,, 2004)
Because cytokines regulate many different bodily functions in living organisms, mainly at the level of cell-cell communications, there is great interest in understanding their mode of action. In Cytokine Protocols, established researchers, physicians, and clinicians present their best biochemical, cellular, and molecular techniques for unraveling and quantifying the events occurring between the initial contact of a cytokine at the membrane receptor and the eventual activation of gene transcription. Described in step-by-step detail to ensure successful experimental results, these protocols cover the large-scale generation and purification of plasmid DNA, the identification of DNA-protein interactions via the gel mobility shift assay, RNA-level phenomena, and the isolation and characterization of cytokines, cytokine-related proteins, and their interactions. The techniques used include the generation of transfectants, the immunohistochemical detection of cytokines in tissue sections, and optimized staining for cytoplasmic detection. Highlights include RT-PCR of small amounts of mRNA, in situ hybridization, biosensor analysis, measurement of biological activities and standardization, immunohistochemical and single-cell detection, and receptor isolation, characterization, and crystallization. Each protocol includes a background introduction, equipment and reagent lists, tips on troubleshooting and avoiding pitfalls, and, where needed, a discussion of the interpretation of results. Comprehensive and highly practical, Cytokine Protocols offers novice researchers a concise introduction to the principles of cytokine research, and experienced investigators all the advanced techniques and time-saving tips needed to ensure productive research.